Residual strength evaluation of Notre Dame surviving masonry after the fire. (April 2021) - Manuello Bertetto, A.; D'Angella, P.; Fronterre', M.
Highlights: Impressive fire devastated the cathedral of Notre Dame in Paris, one of the symbols of European architecture. The residual strength ratio and the compressive strength evolution are evaluated. A CFD model was used to determine the spread of fire and smokes into the roof. Notre Dame safe reconstruction. Abstract: An impressive fire devastated the cathedral of Notre Dame in Paris, one of the symbols of European architecture. The flames spread from the scaffolding embracing the base of the spire on the cathedral roof. The fire blazed up in the church during the religious celebration on April 15th at 6:45 p.m. The fire enveloped abruptly the roof and the spire erected by Viollet-le-Duc in 1860. The collapse took place about 80 min around 8 p.m [1–3 ]. Today, the clamor is all around, the silence is in the heart. At the time of the present paper, the causes of the catastrophe are still wrapped in a dense smoke, like the one generated by the burning "forest"– as the roof structure was called. This is the figure of the disaster. The Cathedral's inferno devastated a world treasure, prompting an outpouring of collective sorrow and soul-searching over whether to recreate the destroyed oak-framed roofing and spire or adapt the cathedral to the 21st century. In the present paper, a computer-based fire simulation model based on Computational Fluid Dynamics (CFD) was used to determine the spread of fire and smokes into the structure of the roof and, at the same time, an original evaluation of the residual strength taking into account the fire effect and the water saturation in the limestone after the extinguishing was estimated. The residual strength ratio ( RSR ) and the compressive strength ( CS ) evolution are carefully evaluated for the injured structures. An estimation of the residual effective strength of the masonry walls of the Cathedral is proposed.